24‐1: Mira Display Processor for AR/VR Systems. Issue 1 (29th May 2019) - Modrzyk, Damian; Martin, Sam; Crawford, Ashley; Starkey, Brian; Vyas, Kushan; Unal, Metin
Abstract : We introduce Mira, a novel display processor targeted at the AR/VR application spectrum employing mobile and head‐mounted display (HMD) SoCs. Mira implements AR/VR processing functions such as asynchronous timewarp, homography and optical distortion corrections in a single‐pass display composition engine. When compared with existing AR/VR systems, where this processing is done on the GPU, our dedicated processor provides a significant reduction in system memory bandwidth and system power, lower motion‐to‐photon latency, better image quality, as well as enables higher resolutions and frame rates that are not possible in GPU‐based systems.